Temperature-related changes in respiration and Q10 coefficient of Guava - Bron Ilana Urbano (Scientia Agricola, 2005)
Guava (Psidium guajava L.) is a tropical fruit that presents fast post-harvest ripening; therefore it is a very perishable product. Inappropriate storage temperature and retail practices can accelerate fruit quality loss. The objective of this study was to evaluate the respiratory activity (RA), the ethylene production (EP) and Q10 of guava fruit at different storage temperatures. 'Paluma' guava fruits were harvested at maturity stage 1 (dark-green skin) and stored at either 1, 11, 21, 31 or 41ºC; RA and EP were determined after 12, 36, 84 and 156 h of storage. RA and EP rates at 1 and 11ºC were the lowest - 0.16 and 0.43 mmol CO2 kg-1 h-1 and 0.003 and 0.019 µmol C2H4 kg-1 h-1, respectively. When guavas were stored at 21ºC, a gradual increase occurred in RA and EP, reaching 2.24 mmol CO2 kg-1 h-1 and 0.20 µmol C2H4 kg-1 h-1, after 156 h of storage. The highest RA and EP were recorded for guavas stored at 31ºC. In spite of high RA, guavas stored at 41ºC presented EP similar to guavas stored at 11ºC, an indicator of heat-stress injury. Considering the 1-11ºC range, the mean Q10 value was around 3.0; the Q10 value almost duplicated at 11-21ºC range (5.9). At 21-31ºC and 31-41ºC, Q10 was 1.5 and 0.8, respectively. Knowing Q10, respiratory variation and ripening behavior in response to different temperatures, fruit storage and retail conditions can be optimized to reduce quality losses.